Gross morphology and histology of the olfactory organ of the Greenland shark Somniosus microcephalus - FERRANDO, SARA; GALLUS, LORENZO; GHIGLIOTTI, LAURA; VACCHI, MARINO; Nielsen, J.; Christiansen, J. S.; PISANO, EVA (Polar Biology, 2016)
The Greenland shark (Somniosus microcephalus) is the largest predatory fish in Arctic waters. Knowledge of the fundamental biology and ecological role of the Greenland shark is limited, and the sensory biology of the Greenland shark has been poorly studied. Given the potential relevant contribution of chemoreception to the sensory capability of the Greenland shark to forage and navigate in low-light environments, we examined the architecture of the peripheral olfactory organ (the olfactory rosette) through morphological, histological and immunohistochemical assays. We found that each olfactory rosette consists of a small number of lamellae (22) associated with a relatively high surface area of the olfactory epithelium. The general organization of the epithelium is similar to that described for other elasmobranchs. However, details that have emerged concerning the cell type composition (absence of crypt neurons, presence of unusually large cells along the olfactory fiber bundles) deserve further investigation. Overall, the structure of the olfactory rosette suggests a well-developed olfactory capability for the Greenland shark coherent with a bentho-pelagic lifestyle.